Effects of tillage practices and nutrient management on crop productivity and profitability in Jute-T. aman rice- onion cropping system (Bangladesh Journal of Agricultural Research, 2019)
Conservation agriculture (CA) with appropriate nutrient management can help increase crop production, improve soil health and bring economic return. An experiment was conducted at farmer’s field of Rajbari district under Low Ganges River Floodplain (AEZ-12) during 2017-2018 to evaluate the effects of tillage and nutrient management on the system productivity and profitability in the jute - T. Aman rice- onion cropping system. Strip tillage (ST) for jute, non-puddling for T. Aman rice and one pass minimum tillage (MT) for onion was contrasted with conventional crop establishment practice (CT). Four different nutrient management practices were NM1: farmer’s practice (FP), NM2: soil test based (STB) fertilizer, NM3:25% extra of STB and NM4: organic amendments (20 % nutrients from cowdung). The experiment was laid out in a split-plot design with three replications by assigning tillage practices in main plots and nutrient management in sub-plots. The yield attributes of jute, T. Aman rice and onion responded similarly to tillage practices. On the other hand, the system productivity and yield of component crops varied due to different nutrient management practices (p